Anti-lipidemic Effect of Fractions of Peristrophe bivalvis Leaf in NG-nitro-L-arginine Methyl Ester (L-NAME) Treated Rats - Aluko, Esther Oluwasola; Omobowale, Temidayo Olutayo; Oyagbemi, Ademola Adetokunbo; Fasanmade, Adesoji Adedipe (Drug Research, 2020)
Purpose The reduction in nitric oxide (NO) bioavailability accelerates atherosclerosis development, augments lipolysis, elevates blood pressure and upregulate leukocyte level. This study was designed to examine the biochemical constituents of fractions of Peristrophe bivalvis (PB) leaf, their effect on blood pressure, serum lipid contents and complete blood count in NG-nitro-L-arginine methyl ester (L-NAME) hypertensive rats.Method Male Wistar rats were grouped into control and hypertensive groups. The hypertensive group was pretreated with 60 mg/kg b.w of L-NAME (L-NAME60) daily for two weeks. They were then randomly sub-grouped into: Hypertensive (H), Hypertensive+n-hexane fraction (HHF), Hypertensive+dichloromethane fraction (HDF), Hypertensive+ethyl acetate fraction (HEF) and Hypertensive+aqueous fraction (HAF) groups. These were orally gavaged with L-NAME60 and L-NAME60+200 mg/kg b.w of fractions of PB respectively, daily for two weeks.Result The biochemical components analysis of the fractions of PB identified numerous polar and non polar compounds like alkaloids, organic acids and esters. The results showed a significant increase in NO level in HHF and HEF groups compared to H. Total cholesterol, triglyceride, low density lipoprotein cholesterol (LDL-C) and very LDL-C were significantly decreased in HAF group compared to H. High density lipoprotein cholesterol (HDL-C) increased significantly and atherogenic indices decreased significantly in HHF, HDF and HAF groups compared to H, while reduced glutathione level increased significantly in HHF group compared to H. White blood cells count effectively decreased in HEF group compared to H.Conclusion In brief, the fractions of PB leaf increased HDL-C and NO, and decrease atherogenic indices in L-NAME treated rats.
Keywords: nitric oxide synthase inhibitor; Peristrophe bivalvis; nitric oxide; lipid contents; blood pressure